Serum Glycomics on Postoperative Day 7 Are Associated With Graft Loss Within 3 Months After Liver Transplantation Regardless of Early Allograft Dysfunction. Issue 11 (November 2021) - Verhelst, Xavier; Geerts, Anja; Colman, Roos; Vanlander, Aude; Degroote, Helena; Abreu de Carvalho, Luis; Meuris, Leander; Berrevoet, Frederik; Rogiers, Xavier; Callewaert, Nico; Van Vlierberghe, Hans
Abstract : Background: Prediction of outcome after liver transplantation (LT) is limited by the lack of robust predictors of graft failure. In this prospective study, we aimed to define a serum glycomic signature in the first week after LT that is associated with graft loss at 3 mo after LT. Methods: Patients were included between January 1, 2011, and February 28, 2017. Glycomic analysis was performed using DNA sequencer-associated fluorophore-associated capillary electrophoresis on a serum sample 1 wk after LT. Making use of Lasso regression, an optimal glycomic signature was identified associated with 3-mo graft survival. Results: In this cohort of 131 patients, graft loss at 3 mo occurred in 14 patients (11.9%). The optimal mode, called the GlycoTransplantTest, yielded an area under the curve of 0.95 for association with graft loss at 3 mo. Using an optimized cutoff for this biomarker, sensitivity was 86% and specificity 89%. Negative predictive value was 98%. Odds ratio for graft loss at 3 mo was 70.211 ( P < 0.001; 95% confidence interval, 10.876-453.231). Conclusions: A serum glycomic signature is highly associated with graft loss at 3 mo. It could support decision making in early retransplantation.